Telemorphosis - Baudrillard, Jean, 1929-2007 (Pharmakon (Minneapolis, Minn.), 2011)
The art of living today has shifted to a continuous state of the experimental. In one of his last texts, Telemorphosis, renowned thinker and anti-philosopher Jean Baudrillard takes on the task of thinking and reflecting on the coming digital media architectures of the social. While "the social" may have never existed, according to Baudrillard, his analysis at the beginning of the twenty-first century of the coming social media-networked cultures cannot be ignored. One need not look far in order to find oneself snared within some sort of screenification of a techno-social community. "What the m.